FEATURES OF THE TEACHER’S INTERACTION WITH STUDENTS IN THE PROCESS OF THEIR PREPARATION FOR SELF-EDUCATION - Cherepanova Г.Л. (Pedagogy of Higher and Secondary Education, 2022)
The author analyses the peculiarities of interaction between the teacher and students in the process of preparation the students to self-education activity.